Effects of rural industrial integration development on the performance of entrepreneurial enterprises of returning college students - Yan Lu; Yun Yu; Guoqing Wu (Humanities & Social Sciences Communications)
Abstract This study used structural equation model (SEM) to investigate the mechanism of integrated development of rural industries (IDRI) on the performance of college students’ returning entrepreneurial enterprises (CSREE). The results show that: (1) IDRI significantly promotes the performance of CSREE, which is consistent with the theory of “sixth industry”. (2) The length, width, and depth of rural industrial integration have a significant effect on CSREE. Among them, the depth of rural industrial integration has the greatest degree of direct influence on CSREE, followed by the width of rural industrial integration, and finally the length of rural industrial integration. (3) IDRI indirectly has a positive impact on the performance of CSREE through internal technological innovation ability and cooperative development ability. Seize the great opportunity of rural integration development to further improve the performance of CSREE. The specific ways are as follows: (1) The government should make overall planning, first determine the local leading industries, establish the whole industrial chain, and give full play to the various functions of agriculture. At the same time, the government should actively guide agricultural enterprises to develop in the direction of internal integration of planting and breeding, three-dimensional agriculture, and other industries, extend the length of the industrial chain, broaden the width of the industrial chain, and deepen the depth of industrial integration, so as to optimize the external environment for college students to return home and start businesses. (2) In the process of returning to their hometowns to start businesses, college students should attach importance to improving internal technological innovation capability and cooperation development capability, cultivate “internal strengths”, and comprehensively improve enterprise performance.